Accountability of Prosecutors in the Management of Evidence and Seized Assets from Criminal Offenses - Calista Eka Triana; Kiki Kristanto; Hilyatul Asfia; Eny Susilowati (Research Horizon, 2026)
The management of evidence and seized assets is a crucial aspect of the criminal justice system because it is closely linked to the evidentiary process, legal certainty, and the preservation of the economic value of confiscated property. This study aims to analyze the accountability of prosecutors in managing evidence and seized assets derived from criminal offenses and to identify the obstacles encountered in their implementation. The study employed an empirical juridical method supported by a literature review approach. Primary data were obtained through interviews with prosecutors, while secondary data were collected from statutory regulations, academic books, and scientific journals. The findings reveal that prosecutorial accountability has generally been implemented in accordance with applicable legal provisions through the stages of receiving, storing, maintaining, returning, destroying, and executing evidence. Internal supervision and the application of the chain of custody principle also contribute to maintaining the integrity of evidence management. However, budget constraints, inadequate infrastructure, and evidence accumulation remain significant challenges. Therefore, strengthening the evidence management system, improving storage facilities, optimizing budget allocation, and enhancing inter-agency coordination are necessary to achieve more professional, accountable, and effective evidence management.